Egy 19. században feltárt honfoglalás kori temető elemzése az új kutatási eredmények tükrében Piliny-Leshegy - Soós Rita (SZTE BTK Régészeti Tanszék Szeged, 2015)
The area of Piliny village was an ideal place for settling in the Hungarian Conquest Period in terms of the type of the soil, the amount of precipitation, vegetation and several other environmental endowments. Artefacts of various age found in this area prove that these conditions were given and suitable for settling, even in the previous periods and through the Middle Ages, respectively, and to the Modern Era. In my research I reconstructed the artefacts and observations of the five grave cemetery of Piliny— Leshegy which was excavated by Baron Jenő Nyáry in 1871.1 also gave a detailed analysis of the types of artefacts that define the character of this archaeological site, because the graves in question hold a distinguished place among the 9th— 11th century archaeological sites of the historic Nógrád County. My work's purpose was to date the site in the most exact way possible. The dating of the first third of 10th century is unproved in view of the archaeological material. In the publication of this burial place we can appreciate not only the first professional excavation of the Hungarian Conquest Period cemeteries, but the start of the archaeological objects' particular and erudite evaluation. In my opinion, we can no longer be sure with absolute confidence that this site belongs to the "burial places of a nuclear family", nor that these graves belong to the "first generations of settlers".
Keywords: Bölcsészettudományok; Történettudomány és régészet